The Impact of the Environmental Quality Label on the Companies Operating Within the Porto Conte Marine Protected Area in Sardinia (Italy) - Zito, Carla; Manca, Gavina (Frontiers in Sustainability, 2021)
The Porto Conte Natural Park, an institution managing and developing the area surrounding the territory of Alghero in Sardinia, decided to join the Park and Protected Area Network Environmental Quality Label (“Marchio di Qualità della Rete dei Parchi e delle Aree Protette”). The label may be awarded to products and accommodation facilities taking special care of the protection of the environmental and local development. In order to evaluate the benefits of this initiative on the companies operating within the park, a survey was administered among the companies awarded with the label and the local community. The companies recognized the benefits thereof, mostly in terms of reputation, as a result of the adoption of responsible environmental behaviors by the members of the business organization. In addition, greater attention to environmental protection resulted in a decrease of waste production and a rigorous compliance with the applicable rules and regulations. Most of the companies interviewed were generally satisfied with the park's project but complained about the poor advertising initiatives by the Park's Managing Body. As a matter of fact, about the 50% of the residents interviewed were not aware of the label award and the product certification. Considering that the residents of the park area are sensitive to environmental issues, and they believe that the park is a major asset for the area, better communication, and a greater involvement of all stakeholders in the initiative undertaken by the Park's Managing Body may help companies expand their business also locally.